Teachers’ Support and Its Effect on Students’ Learning Motivation - Pangestu, Desi; Meiristiani, Noeris; Laela Risky, Afifah; Rizka Rahmadhani, Mawar (Universitas Jambi, Magister Program of English Education Department, 2025)
This study investigates the role of teacher support in shaping English as a Foreign Language (EFL) learners’ motivation through a structured literature review. Psychological and social factors, especially teacher support, are critical in enhancing student motivation, particularly in settings where learners face anxiety or low confidence. The review focuses on three core types of teacher support, emotional, academic, and autonomy-supportive and their contributions to student engagement and language learning motivation. Ten peer-reviewed articles published between 2014 and 2025 were analyzed using thematic content analysis to identify patterns in findings, methods, and cultural contexts. Results show that teacher support consistently enhances motivation, with integrated support having the strongest impact. The novelty of this study lies in its cross-cultural synthesis and emphasis on the need for integrated and longitudinal approaches. Findings suggest that teacher training programs should adopt holistic strategies to foster and maintain student motivation in EFL classrooms.